To solve this system of equations, we can use the substitution or elimination method.
1. Substitution method:
From the first equation, we can solve for y:
y = -2x - 2
Now, substitute this into the second equation:
2x - 2(-2x - 2) = 5
2x + 4x + 4 = 5
6x + 4 = 5
6x = 1
x = 1/6
Now that we have found the value of x, we can substitute it back into the first equation to find the value of y:
y = -2(1/6) - 2
y = -1/3 - 2
y = -2 1/3
Therefore, the solution to the system of equations is:
x = 1/6
y = -2 1/3
y=-2x -2
2x -2y =5
1 answer